Sensor Based Shopping using Eye-Blink and IoT Technology - V.Priyadharshini; Jebarani, T. Sneha; Vaishnavi, T.M.; Kanagavalli, M. (IRO Journal on Sustainable Wireless Systems, 2024)
The proposed research is an innovative system designed to enhance the shopping experience for physically challenged individuals. The system makes use of relay motors, LCD displays, and Arduino-based eye-blink sensors to provide a user-friendly interface that enables people with physical limitations to explore and engage with shopping environments. Additionally, IoT is used for user interaction. The main functionality of the system is based on eye-blink technology. By detecting eye blinks, the sensors interpret user commands, enabling individuals to control shopping cart movement, and select items from shelves.